1998
DOI: 10.1029/98jb01554
|View full text |Cite
|
Sign up to set email alerts
|

Joint estimation of afterslip rate and postseismic relaxation following the 1989 Loma Prieta earthquake

Abstract: Abstract. Global Positioning System (GPS) data from campaigns carried out over the 5 years following the 1989 Loma Prieta earthquake and leveling data measured in 1990 and 1992 define the postseismic velocity field around the Loma Prieta rupture zone. Subtraction of a background velocity field yields a residual velocity pattern which we interpret as the product of two physical processes: (1) slow afterslip along distinct planes in the upper cru, st and (2) viscoelastic relaxation of the lower crust and upper m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 49 publications
10
100
2
Order By: Relevance
“…For example, a Maxwell time t = h/G, with t = 50 days and a shear modulus for lower continental crust of G = 40 GPa, leads to a dynamic viscosity h of around 1 Â 10 17 Pa s for the lower crust. This is 1 -2 orders of magnitude smaller than expected for the lithosphere [Pollitz and Bürgmann, 1998;Viti et al, 2003]. That is, the timescale of our problem (50 days) is 1 or 2 orders of magnitude too short to be related to viscous behavior of a relatively cold, lower continental crust.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, a Maxwell time t = h/G, with t = 50 days and a shear modulus for lower continental crust of G = 40 GPa, leads to a dynamic viscosity h of around 1 Â 10 17 Pa s for the lower crust. This is 1 -2 orders of magnitude smaller than expected for the lithosphere [Pollitz and Bürgmann, 1998;Viti et al, 2003]. That is, the timescale of our problem (50 days) is 1 or 2 orders of magnitude too short to be related to viscous behavior of a relatively cold, lower continental crust.…”
Section: Discussionmentioning
confidence: 74%
“…[31] Postseismic viscous relaxation processes [Pollitz and Bürgmann, 1998;Viti et al, 2003] can be excluded because of the short timescale of the observation. For example, a Maxwell time t = h/G, with t = 50 days and a shear modulus for lower continental crust of G = 40 GPa, leads to a dynamic viscosity h of around 1 Â 10 17 Pa s for the lower crust.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing GPS and leveling data following the 1989 Loma Prieta, California, earthquake (M = 7.1), Pollitz et al (1998) found that both postseismic sliding and viscoelastic relaxation of the lower crust and upper mantle occurs and the former effect is predominant in postseismic surface deformation. Similar conclusion was obtained for the 1994 Northridge earthquake, California, of M = 6.7 by Donnellan and Lyzenga (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there should be some time variation in crustal straining in the period between two large recurring earthquakes due to both frictional afterslip and ductile flow (e.g., Cohen, 1999;Pollitz et al, 1998;Smith and Wyss, 1968). In the case of the Himalayas, a strong asymmetry of the postseismic relaxation should be expected due to the presumably much lower viscosity beneath southern Tibet.…”
Section: A Model Of the Seismic Cycle In The Central Nepal Himalayasmentioning
confidence: 98%